PENERAPAN MODEL ROLE PLAYING UNTUK MENINGKATKAN KERJASAMA DAN HASIL BELAJAR PESERTA DIDIK - Jauhariatun, Viera Zahra; Sunarya, Dede Tatang; Hanifah, Nurdinah (Jurnal Pena Ilmiah, 2019)
This research aims to know the application of role playing model can enhance cooperation and student learning outcomes in Social Science subjects in class V D Tegalkalong SDN.Â  The research method used i.e., class Act (PTK). Subjects in the study are grade V D SDN Tegalkalong that add up to 29 students. This research was carried out in three cycles. The increased cooperation of the students characterized by an increase in the percentage of each aspect of the cooperation of pre stage action to cycle 3, cycle 1 as much as 54%, 71% of the number of cycle 2 and cycle 3, reaches 100%. Improved student learning outcomes are characterized by an increase in the percentage of each aspect of the results of the study of the stages of the pre an action until the cycle 3, cycle 1 reaches 78%, reaching 83% of cycle 2 and cycle 3, reaching 100%. So that corrective actions were stopped on 3rd cycle due to the already very reasonably meet the expected targets on this research.